Scarlet Witch. Vol. 3, The final hex - Robinson, James, 1963- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2017)
The SCARLET WITCH travels to SERBIA to dive deep into her Romany roots! Who were her parents? Where does she come from? Wanda will discover the answers...and seek her revenge! COLLECTING: SCARLET WITCH 11-14, UNCANNY AVENGERS ANNUAL 1